Determinants of Early Detection Service Utilization for Hepatitis B among Pregnant Women: A Study from Semarang City, Indonesia - Adilah, Annida Nur; Sriatmi, Ayun; Nandini, Nurhasmadiar (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Hepatitis B remains a major global health challenge, with mother-to-child transmission contributing significantly to chronic infection and severe complications. In Indonesia, despite national targets of 95% coverage, screening rates among pregnant women in Semarang City remain suboptimal, with limited evidence on the determinants of service utilization. This study aimed to identify factors associated with the utilization of hepatitis B early detection services among pregnant women in Semarang City. A quantitative cross-sectional design was employed, using primary data collected through structured interviews with 200 respondents selected purposively. Data analysis was conducted using chi-square tests to examine associations between independent variables and screening utilization. The findings revealed that maternal attitude (p=0.006), health worker support (p=0.001), perception of service procedures (p=0.023), access to information (p=0.045), healthcare access (p=0.007), and perceived severity (p=0.008) were significantly associated with service utilization. In contrast, maternal education, employment status, knowledge, family support, and perceived susceptibility showed no significant association. These findings highlight the importance of behavioral and system-level factors in improving screening coverage through strengthened counseling, better service delivery, expanded information access, and equitable healthcare. Moreover, early detection aligns with Islamic values of Hifz an-nasl by protecting maternal and child health, where faith-based and community-centered strategies can enhance family health and accelerate hepatitis B elimination.